Two Complex Graph Operations and their Exact Formulations on Topological Properties. (7th June 2022) - Hameed, Shehla; Jamil, Muhammad Kamran; Waheed, Muhammad; Azeem, Muhammad; Swaray, Senesie
Abstract : Graph operations are utilized for developing complicated graph structures from basic graphs, and these basic graphs can help to understand the properties of complex networks. While on the other side, the topological descriptor is known as a numeric value that is associated with the graph of a network. It has enormous practical applications in chemistry and other fields of science. This particular work in this draft is the extended work and investigated the first, second, first multiplicative, first reformulated Zagreb indices, and the forgotten index of subdivision double corona and subdivision double neighborhood corona products.